Profil Umbi Uwi (Dioscorea alata) dan Potensi Aplikasi Pada Beragam Produk Pangan: Review - Mojiono Mojiono; Mia Dewi Surya Ajiid; Sri Wulandari; Feti Apriliyanti; Fajar Alamsyah; Hamzah Fansuri (Universitas Islam Madura, 2022)
The aim of this review is to determine the profile of yam tubers and their potential for food products. Yam (Dioscorea alata) is one of potential plants producing carbohydrate-rich tubers with short and coarse root hairs. The flesh color of the yam tubers can vary greatly, including white and purple. The carbohydrate content of yam tuber is high, ranging from 72.6-80.2% of the dry weight. Besides containing carbohydrates, yam tubers also contain bioactive components such as dioscin, dioscorin, allantoin, choline, polyphenols, and diosgenin. The granular shape of yam is generally oval, triangular, round and polygonal with the size ranging from 10-41.5 µm. The highest chemical composition of yam tubers was moisture and starchy component. Yam starch can be applied in various processed products such as instant noodles, analog rice, and ice cream. The low glycemic index of the yam can be beneficial for development of low GI instant noodles compared to other types of instant noodles. In addition, yam tubers can also be processed into analogue rice with a fairly high carbohydrate content.